A metastable beta titanium alloy and a method of making the same

CN123027477APending Publication Date: 2026-11-03CHINA FIRST HEAVY IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611265389.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

In engineering applications, existing metastable β-titanium alloys have difficulty simultaneously improving yield strength and tensile strength, resulting in irreversible plastic deformation in the early stages of service, low strength utilization, and inability to fully leverage the performance advantages of high-load-bearing structural components.

Method used

By limiting the specific molar ratio of the five elements Ti, Nb, Cr, Fe, and Si, an alloy system with excellent β-phase stability was constructed. The cold rolling-ultra-fast heating reverse phase transformation process was used to achieve extreme refinement of the alloy microstructure and improvement of its strength.

Benefits of technology

This study achieved a significant simultaneous increase in the yield strength and tensile strength of metastable β-titanium alloys, breaking through the strength improvement bottleneck in traditional processes, obtaining high-density martensite and deformation twin structures, and enhancing the overall performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027477A_ABST
    Figure CN123027477A_ABST
Patent Text Reader

Abstract

The application provides a metastable beta titanium alloy and a preparation method thereof, and relates to the technical field of alloy materials.The metastable beta titanium alloy comprises Ti elements, Nb elements, Cr elements, Fe elements and Si elements, and the molar ratio of the Ti elements, the Nb elements, the Cr elements, the Fe elements and the Si elements is (84-88):(8-10):(2-3):(2-3):(0.1-0.2).The application constructs a metastable alloy system with excellent beta phase stability by limiting the specific molar ratio of the five elements Ti, Nb, Cr, Fe and Si, and realizes the synchronous substantial improvement of the yield strength and the tensile strength of the metastable beta titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials technology, and more specifically, to a metastable β-titanium alloy and its preparation method. Background Technology

[0002] Titanium alloys, due to their low density, high specific strength, excellent corrosion resistance, and good biocompatibility, have become indispensable key structural materials in aerospace, marine engineering, and high-end medical devices. Among them, metastable β titanium alloys, containing a large number of β-stabilizing elements, can retain a completely β single-phase microstructure after quenching to room temperature. During subsequent plastic deformation, they exhibit significant work hardening through stress-induced martensitic transformation (TRIP effect) and deformation twinning (TWIP effect), thus demonstrating excellent plasticity potential.

[0003] However, despite the aforementioned excellent intrinsic properties of metastable β-titanium alloys, they still face significant mechanical performance bottlenecks in engineering applications. The yield strength and tensile strength of these alloys are often difficult to increase simultaneously to high levels, lacking an effective synergistic gain mechanism between them. In practical applications, this generally manifests as low yield strength, leading to irreversible plastic deformation in the early stages of service; or, although tensile strength is improved, the increase in yield strength is limited, resulting in low strength utilization and failing to fully realize their performance advantages as high-load-bearing structural components. This phenomenon of "low strength and low yield ratio" severely restricts the widespread application of metastable β-titanium alloys in high-end, demanding working conditions. Currently, a mature and universally applicable technical solution has not yet been developed to address this mechanical performance bottleneck, effectively breaking the mutual constraint between yield strength and tensile strength while ensuring basic material processing performance. Therefore, obtaining a metastable β-titanium alloy with both high yield strength and high tensile strength remains a pressing technical challenge in this field. Summary of the Invention

[0004] The problem solved by this invention is: how to obtain a metastable β-titanium alloy that has both high yield strength and high tensile strength.

[0005] To address the aforementioned problems, this invention provides a metastable β-titanium alloy comprising: Ti, Nb, Cr, Fe, and Si, wherein the molar ratio of Ti, Nb, Cr, Fe, and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2).

[0006] Compared with related technologies, this invention constructs a metastable alloy system with excellent β-phase stability by limiting the specific molar ratio of the five elements Ti, Nb, Cr, Fe, and Si. Nb, as a isomorphous β-stabilizing element, ensures a fully β-single-phase microstructure at room temperature; Cr and Fe, as strong β-eutectoid elements, synergistically lower the β-transformation temperature and provide solid solution strengthening; trace amounts of Si segregate at grain boundaries, inhibiting grain growth and introducing grain boundary strengthening. This compositional design effectively overcomes the defects of insufficient β-phase stability or brittle phase precipitation in traditional metastable β-titanium alloys. More importantly, it lays the microstructural foundation for inducing high-density martensite and deformation twins during subsequent cold rolling, as well as the interface memory effect during rapid heating. Furthermore, through the synergistic effect of ultrafine grain strengthening and solid solution strengthening, a simultaneous and significant increase in the yield strength and tensile strength of the metastable β-titanium alloy is achieved.

[0007] This invention also provides a method for preparing a metastable β-titanium alloy, comprising: Step S1: Prepare a metastable β-titanium alloy slab; wherein, in the metastable β-titanium alloy slab, the molar ratio of Ti, Nb, Cr, Fe and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2); Step S2: Perform at least one cold rolling-heating reverse phase transformation treatment on the metastable β titanium alloy slab to obtain the metastable β titanium alloy; The cold rolling-heating reverse phase transformation treatment includes: The metastable β-titanium alloy slab was subjected to multiple cold rolling passes at room temperature. The cold-rolled slab is heated to a preset temperature at a heating rate of 100℃ / s to 300℃ / s and then quenched to room temperature; wherein, the preset temperature T β -30℃ to T β T β The β transformation temperature is the value of the metastable β-titanium alloy slab.

[0008] Compared with related technologies, this invention, based on the aforementioned specific composition design, achieves extreme refinement of the alloy microstructure and simultaneous improvement of strength through a "cold rolling-ultra-rapid heating reverse phase transformation" process. First, room temperature multi-pass cold rolling induces high-density deformation in the matrix, generating martensite and deformation twins, providing sufficient deformation energy storage and active interfaces for the subsequent reverse phase transformation. Second, an ultra-high heating rate of 100℃ / s to 300℃ / s effectively suppresses grain recovery and growth during heating, and utilizes the interface memory effect to drive the deformation-induced rapid reverse phase transformation from martensite to β phase. Subsequently, quenching locks the ultrafine-grained β phase microstructure at high temperature, ultimately obtaining a submicron to micron-scale (0.5μm to 3μm) ultrafine-grained heterostructure. This structure, through the Hall-Petch strengthening effect, achieves a synergistic leap in yield strength and tensile strength, successfully overcoming the bottleneck of simultaneously improving the strength of metastable β titanium alloys.

[0009] Optionally, in step S2, the cumulative cold rolling deformation of the metastable β-titanium alloy slab is 30% to 65%.

[0010] Optionally, in step S2, the reduction in each pass of the multi-pass cold rolling is 0.05 mm to 0.15 mm.

[0011] Optionally, in step S1, the preparation of the metastable β-titanium alloy slab includes: Ingots are obtained by smelting Ti, Nb, Cr, Fe, and Si as raw materials; The ingot is subjected to initial forging, intermediate forging and final forging in sequence to obtain the metastable β titanium alloy slab.

[0012] Optionally, the melting is carried out under vacuum conditions, and the melting is performed 4 to 6 times.

[0013] Optionally, the termination temperature for each melting is 2500°C to 3000°C, and the melting time for each melting is 6 min to 10 min.

[0014] Optionally, the temperature of the forging is 1100°C to 1200°C, and the deformation of the forging is 30% to 50%.

[0015] Optionally, the intermediate forging temperature is 950°C to 1050°C, and the deformation amount of the intermediate forging is 30% to 50%.

[0016] Optionally, the final forging temperature is 800°C to 900°C, and the final forging deformation is 30% to 50%. Attached Figure Description

[0017] Figure 1The image shown is a transmission electron microscope (TEM) image of the metastable β-titanium alloy sample prepared in Example 1 of this invention. Figure 2 The image shown is a transmission electron microscope (TEM) image of the metastable β-titanium alloy sample prepared in Example 2 of this invention. Figure 3 The image shown is a transmission electron microscope image of the metastable β-titanium alloy sample prepared in Example 3 of this invention. Figure 4 The image shows the metallographic structure of the metastable β-titanium alloy sample prepared in Comparative Example 1 of this invention. Detailed Implementation

[0018] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Although some embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the accompanying drawings and embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0019] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0020] The term "comprising" and its variations as used herein are open-ended, meaning "including but not limited to"; the term "based on" means "at least partially based on"; the term "one embodiment" means "at least one embodiment"; the term "another embodiment" means "at least one additional embodiment"; the term "some embodiments" means "at least some embodiments"; and the term "optionally" means "optional embodiments". Definitions of other terms will be given in the following description. It should be noted that the concepts of "first," "second," etc., mentioned in this invention are used to distinguish different objects, not to describe a specific order or hierarchy. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined with "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0021] An embodiment of the present invention provides a metastable β-titanium alloy comprising: Ti, Nb, Cr, Fe, and Si, wherein the molar ratio of Ti, Nb, Cr, Fe, and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2).

[0022] This invention constructs a metastable alloy system with excellent β-phase stability by limiting the specific molar ratio of the five elements Ti, Nb, Cr, Fe, and Si. Nb, as a isomorphous β-stabilizing element, ensures a fully β-single-phase microstructure at room temperature; Cr and Fe, as strong β-eutectoid elements, synergistically lower the β-transformation temperature and provide solid solution strengthening; trace amounts of Si segregate at grain boundaries, inhibiting grain growth and introducing grain boundary strengthening. This compositional design effectively overcomes the defects of insufficient β-phase stability or brittle phase precipitation in traditional metastable β-titanium alloys. More importantly, it lays the microstructural foundation for inducing high-density martensite and deformation twins during subsequent cold rolling, as well as the interface memory effect during rapid heating. Furthermore, through the synergistic effect of ultrafine grain strengthening and solid solution strengthening, a simultaneous and significant increase in the yield strength and tensile strength of the metastable β-titanium alloy is achieved.

[0023] This invention also provides a method for preparing a metastable β-titanium alloy, comprising: Step S1: Prepare a metastable β-titanium alloy slab; wherein, in the metastable β-titanium alloy slab, the molar ratio of Ti, Nb, Cr, Fe and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2); Step S2: Perform at least one cold rolling-heating reverse phase transformation treatment on the metastable β titanium alloy slab to obtain the metastable β titanium alloy; The cold rolling-heating reverse phase transformation treatment includes: The metastable β-titanium alloy slab was subjected to multiple cold rolling passes at room temperature. The cold-rolled slab is heated to a preset temperature at a heating rate of 100℃ / s to 300℃ / s and then quenched to room temperature; wherein, the preset temperature T β -30℃ to T β T β The β-transformation temperature is the temperature at which the metastable β-titanium alloy slab is formed. It should be noted that the β-transformation temperature (T2) of the metastable β-titanium alloy slab is... β The result can be routinely determined using differential scanning calorimetry (DSC). For example, the heating is performed using pulsed current induction heating.

[0024] Based on the aforementioned specific composition design, this invention achieves extreme microstructural refinement and simultaneous strength enhancement of the alloy through a "cold rolling-ultra-rapid heating reverse phase transformation" process. First, room temperature multi-pass cold rolling induces high-density deformation in the matrix, generating martensite and deformation twins, providing sufficient deformation energy and active interfaces for the subsequent reverse phase transformation. Second, an ultra-high heating rate of 100℃ / s to 300℃ / s effectively suppresses grain recovery and growth during heating, and utilizes the interface memory effect to drive the rapid reverse phase transformation from martensite to β phase induced by deformation. Subsequently, quenching locks in the ultrafine-grained β phase microstructure at high temperature, ultimately obtaining a submicron to micron-scale (0.5μm to 3μm) ultrafine-grained heterostructure. This structure, through the Hall-Petch strengthening effect, achieves a synergistic leap in yield strength and tensile strength, successfully overcoming the bottleneck of simultaneously improving the strength of metastable β titanium alloys.

[0025] In some embodiments of the present invention, in step S2, the cumulative cold rolling deformation of the metastable β-titanium alloy slab is 30% to 65%. This embodiment, by limiting the cumulative cold rolling deformation to 30% to 65%, ensures a balance between sufficient deformation energy storage and microstructure refinement during cold rolling. This provides a sufficient active interface for the martensite → β reverse transformation while avoiding processing defects, thereby synergistically improving the yield strength and tensile strength of the alloy.

[0026] In some embodiments of the present invention, in step S2, the reduction in pressure per pass of the multi-pass cold rolling is 0.05 mm to 0.15 mm. This embodiment achieves stability and deformation uniformity in the multi-pass cold rolling process by limiting the reduction in pressure per pass to 0.05 mm to 0.15 mm. A smaller reduction in pressure per pass (>0.05 mm) avoids plate cracking caused by stress concentration during a single rolling pass, while ensuring a stable and controllable rolling process; while a reduction of no more than 0.15 mm effectively prevents macroscopic shear bands introduced by excessive local shear deformation, ensuring a uniform distribution of deformation-induced martensite and dislocation structures. This "small reduction, multi-pass" rolling mode provides uniform and high-density nucleation sites for the interface memory effect during subsequent rapid heating, which is a key process guarantee for achieving an ultrafine grain structure.

[0027] In some embodiments of the present invention, step S1, the preparation of metastable β-titanium alloy slab, includes: Ingots are obtained by smelting Ti, Nb, Cr, Fe, and Si as raw materials; The ingot is subjected to initial forging, intermediate forging and final forging in sequence to obtain the metastable β titanium alloy slab.

[0028] In some embodiments of the present invention, the melting is carried out under vacuum conditions, and the number of melting cycles is 4 to 6, with each melting cycle ending at a temperature of 2500°C to 3000°C and a melting time of 6 to 10 minutes. This embodiment ensures high uniformity and purity of the alloy composition through a multi-frequency, ultra-high temperature melting process under high vacuum. The repeated melting of 4 to 6 times effectively eliminates segregation and shrinkage defects in the as-cast structure; the ultra-high melting temperature of 2500°C to 3000°C is significantly higher than the melting points of high-melting-point elements such as Nb and Cr, ensuring sufficient melting and diffusion of alloying elements. The ingot prepared by this process has minimal compositional segregation, laying a solid foundation for obtaining a uniform β-phase structure during subsequent forging and heat treatment, and avoiding performance inhomogeneity caused by compositional fluctuations from the source.

[0029] In some embodiments of the present invention, the initial forging temperature is 1100°C to 1200°C, and the deformation amount is 30% to 50%; the intermediate forging temperature is 950°C to 1050°C, and the deformation amount is 30% to 50%; the final forging temperature is 800°C to 900°C, and the deformation amount is 30% to 50%. This embodiment employs a three-stage forging process, achieving progressive crushing and densification of the ingot structure through coordinated control of temperature reduction and deformation amount. The initial forging stage utilizes the high plasticity at high temperatures to fully crush coarse cast grains; the intermediate forging further refines the structure and eliminates internal stress; the final forging stage is carried out in the region close to the β-transformation temperature, effectively controlling the final grain size and shaping. The 30% to 50% deformation amount design at each stage ensures a sufficient forging ratio to weld internal defects while avoiding the risk of cracking due to excessive deformation. The slabs prepared by this process not only have a uniform and dense structure, but also low residual stress, providing an excellent basis for subsequent processing.

[0030] The present invention will be further described below with reference to specific embodiments. It should be noted that water quenching refers to a quenching process in which a heated slab is directly contacted with liquid water and cooled to room temperature.

[0031] Example 1 A1. After uniformly mixing Ti, Nb, Cr, Fe and Si in a molar ratio of 85.85:10:2:2:0.15, the mixture is placed in a vacuum melting furnace for 5 meltings to obtain an ingot. The starting temperature of each melting is room temperature, the ending temperature is 2800℃, and the melting time is 7 minutes.

[0032] A2. The ingot is subjected to initial forging, intermediate forging, and final forging in sequence to obtain a metastable β-titanium alloy slab; wherein the thickness of the metastable β-titanium alloy slab is 10 mm and the width is 150 mm; the initial forging temperature is 1150℃ and the deformation amount of the initial forging is 40%; the intermediate forging temperature is 1000℃ and the deformation amount of the intermediate forging is 40%; the final forging temperature is 850℃ and the deformation amount of the final forging is 40%; the β transformation temperature of the metastable β-titanium alloy slab is determined by DSC to be 795℃.

[0033] A3. The metastable β-titanium alloy slab is subjected to multiple cold rolling passes at room temperature to reduce the slab thickness from 10 mm to 3.9 mm (cumulative cold rolling deformation is 61%). Subsequently, the cold-rolled slab is heated to a preset temperature by pulse current induction heating at a heating rate of 150℃ / s, held at that temperature for 2s, and then water quenched to obtain a metastable β-titanium alloy sample. The preset temperature is 775℃, and the reduction in thickness per pass of the multiple cold rolling passes is 0.1 mm.

[0034] The transmission electron microscopy characterization results of the metastable β-titanium alloy sample prepared in Example 1 are shown in the figure. Figure 1 ,from Figure 1 It can be seen that the microstructure of this metastable β-titanium alloy sample consists of ultrafine grains with a grain size of 2μm to 3μm.

[0035] Example 2 The difference from Example 1 is that step A3 is: The metastable β-titanium alloy slab is subjected to a first multi-pass cold rolling at room temperature to reduce the slab thickness from 10 mm to 6.5 mm (cumulative cold rolling deformation of 35%). Subsequently, the cold-rolled slab is heated to a first preset temperature by pulse current induction heating at a heating rate of 150 °C / s, held at that temperature for 2 seconds, and then water-quenched to obtain a first intermediate slab. The first preset temperature is 775 °C, and the reduction in pressure per pass of the first multi-pass cold rolling is 0.1 mm.

[0036] The first intermediate slab is subjected to a second multi-pass cold rolling at room temperature to reduce the slab thickness to 3.9 mm (the deformation of the second multi-pass cold rolling is 40%, and the cumulative cold rolling deformation is 61%). Subsequently, the cold-rolled slab is heated to a second preset temperature by pulse current induction heating at a heating rate of 200℃ / s and then water quenched to obtain a metastable β titanium alloy sample; wherein, the second preset temperature is 770℃; and the reduction in pressure per pass of the second multi-pass cold rolling is 0.1 mm.

[0037] The transmission electron microscopy characterization results of the metastable β-titanium alloy sample prepared in Example 2 are shown in the figure. Figure 2 ,from Figure 2It can be seen that the microstructure of this metastable β-titanium alloy sample consists of ultrafine grains with a grain size of about 1.5 μm, and a large number of dislocation pile-ups were observed at the grain boundaries.

[0038] Example 3 The difference from Example 1 is that step A3 is: The metastable β-titanium alloy slab is subjected to a first multi-pass cold rolling at room temperature to reduce the slab thickness from 10 mm to 7 mm (cumulative cold rolling deformation is 30%). Subsequently, the cold-rolled slab is heated to a first preset temperature by pulse current induction heating at a heating rate of 150℃ / s, held at that temperature for 1s, and then water-quenched to obtain a first intermediate slab. The first preset temperature is 770℃, and the reduction in pressure per pass of the first multi-pass cold rolling is 0.1 mm.

[0039] The first intermediate slab is subjected to a second multi-pass cold rolling at room temperature to reduce the slab thickness to 4.9 mm (the deformation of the second multi-pass cold rolling is 30%, and the cumulative cold rolling deformation is 51%). Subsequently, the cold-rolled slab is heated to a second preset temperature by pulse current induction heating at a heating rate of 150℃ / s and then water quenched to obtain a second intermediate slab, wherein the second preset temperature is 765℃; the reduction amount of each pass of the second multi-pass cold rolling is 0.1 mm.

[0040] The second intermediate slab is subjected to a third multi-pass cold rolling at room temperature to reduce the slab thickness to 3.9 mm (the deformation of the third multi-pass cold rolling is 20%, and the cumulative cold rolling deformation is 61%). Subsequently, the cold-rolled slab is heated to a third preset temperature by pulse current induction heating at a heating rate of 150℃ / s, held at that temperature for 0.5s, and then water quenched to obtain a metastable β titanium alloy sample, wherein the third preset temperature is 760℃; the reduction in pressure per pass of the third multi-pass cold rolling is 0.1 mm.

[0041] The transmission electron microscopy characterization results of the metastable β-titanium alloy sample prepared in Example 3 are shown in the figure. Figure 3 ,from Figure 3 It can be seen that the microstructure of this metastable β-titanium alloy sample consists of ultrafine grains with a grain size of 0.5 μm to 1.5 μm, and a large number of dislocation entanglements and pile-ups are distributed within the grains and at the grain boundaries. This indicates that while the multiple cycle treatments further refine the grains, they also introduce high-density geometrically necessary dislocations, providing a microstructure basis for the high strength of the alloy.

[0042] Comparative Example 1 (Conventional Heating) The difference from Example 1 is that step A3 is: The metastable β-titanium alloy slab was subjected to multiple cold rolling passes at room temperature to reduce the slab thickness from 10 mm to 3.9 mm (cumulative cold rolling deformation of 61%). Subsequently, the cold-rolled slab was heated to a preset temperature in a conventional heating furnace at a heating rate of 10 °C / s, held at that temperature for 30 min, and then water quenched to obtain a metastable β-titanium alloy sample. The preset temperature was 775 °C, and the reduction in thickness per pass of the multiple cold rolling was 0.1 mm.

[0043] Metallographic analysis was performed on the metastable β-titanium alloy sample prepared in Comparative Example 1. The results are shown in the figure. Figure 4 ,Depend on Figure 4 It can be seen that the microstructure of the sample is composed entirely of equiaxed β grains with an average grain size of about 60 μm. This indicates that conventional slow heating and long-term heat preservation will lead to significant grain coarsening, which is in stark contrast to the 0.5 μm to 3 μm ultrafine grain structure obtained by the ultra-fast heating process of this invention. This verifies the breakthrough effect of the process of this invention in grain refinement. Figure 4 The scale bar represents 75μm.

[0044] Effect Example The tensile strength and yield strength of the metastable β titanium alloy samples prepared in Examples 1 to 3 and Comparative Example 1 were tested. The results are shown in Table 1. As can be seen from Table 1, compared with Comparative Example 1, the tensile strength and yield strength of the metastable β titanium alloy samples prepared in Examples 1 to 3 are higher. Compared with Examples 1 and 2, the tensile strength and yield strength of the metastable β titanium alloy sample prepared in Example 3 are higher.

[0045] Table 1

[0046] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. A metastable β-titanium alloy, characterized in that, include: The elements are Ti, Nb, Cr, Fe, and Si, wherein the molar ratio of Ti, Nb, Cr, Fe, and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2).

2. A method for preparing a metastable β-titanium alloy, characterized in that, include: Step S1: Prepare a metastable β-titanium alloy slab; wherein, in the metastable β-titanium alloy slab, the molar ratio of Ti, Nb, Cr, Fe and Si is (84 to 88): (8 to 10): (2 to 3): (2 to 3): (0.1 to 0.2); Step S2: Perform at least one cold rolling-heating reverse phase transformation treatment on the metastable β titanium alloy slab to obtain the metastable β titanium alloy; The cold rolling-heating reverse phase transformation treatment includes: The metastable β-titanium alloy slab was subjected to multiple cold rolling passes at room temperature. The cold-rolled slab is heated to a preset temperature at a heating rate of 100℃ / s to 300℃ / s and then quenched to room temperature; wherein, the preset temperature T β -30℃ to T β T β The β transformation temperature is the value of the metastable β-titanium alloy slab.

3. The method for preparing metastable β-titanium alloy according to claim 2, characterized in that, In step S2, the cumulative cold rolling deformation of the metastable β-titanium alloy slab is 30% to 65%.

4. The method for preparing metastable β-titanium alloy according to claim 2, characterized in that, In step S2, the reduction in pressure per pass of the multi-pass cold rolling is 0.05 mm to 0.15 mm.

5. The method for preparing metastable β-titanium alloy according to claim 2, characterized in that, In step S1, the preparation of the metastable β-titanium alloy slab includes: Ingots are obtained by smelting Ti, Nb, Cr, Fe, and Si as raw materials; The ingot is subjected to initial forging, intermediate forging and final forging in sequence to obtain the metastable β titanium alloy slab.

6. The method for preparing metastable β-titanium alloy according to claim 5, characterized in that, The melting is carried out under vacuum conditions, and the melting is performed 4 to 6 times.

7. The method for preparing metastable β-titanium alloy according to claim 6, characterized in that, The final temperature for each melting process is 2500℃ to 3000℃, and the melting time for each process is 6 to 10 minutes.

8. The method for preparing metastable β-titanium alloy according to claim 5, characterized in that, The temperature of the forging process is 1100°C to 1200°C, and the deformation of the forging process is 30% to 50%.

9. The method for preparing metastable β-titanium alloy according to claim 5, characterized in that, The intermediate forging temperature is 950°C to 1050°C, and the deformation amount of the intermediate forging is 30% to 50%.

10. The method for preparing metastable β-titanium alloy according to claim 5, characterized in that, The final forging temperature is 800°C to 900°C, and the final forging deformation is 30% to 50%.